The Influence of Human Resource Competence on the Performance of Micro Enterprises in Alewadeng Village - Nur Indah Sari; Anwar Anwar; Agung Widhi Kurniawan (Universitas Negeri Makassar, 2022)
This study aims to examine and analyze the effect of HR competence on the performance of micro-enterprises in Alewadeng Village. The source of data in this study is primary data obtained by distributing questionnaires to respondents. The population is 49 micro business actors in Alewadeng Village which is also a sample (saturated sampling). The analytical method used is simple regression analysis with SPSS (Statistical Product and Service Solutions) tools. The results of the study indicate that the competence of human resources has a positive and significant effect on the performance of micro-enterprises, which means that the better the competence of human resources, the better the business performance.